Ant developer's handbook - Williamson, Alan (Alan R.) (Developer's library., 2003)
Ant has emerged as the preferred building tool for Java developers, automating tedious compilation, test, and code management. Many Java developers are aware of Ant but there is little documentation to assist in getting started with the Ant tool. Even experienced developers who already use some of the features of the Ant tool, struggle with the more advanced aspects. This book will educate those devlopers in these more advanced topics, and help them get more out of the tool. The Ant Developer's Handbook begins with a rapid introduction to obtaining, installing, and configuring Ant and covers all major feature sets and use practices. Ant is a cross-platform build and configuration management tool. It is written in Java, and uses XML as its file format, thereby allowing entire development teams to share Ant build files, regardless of the operating system each developer is using. Ant can perform nearly any common configuration management function, including: compiling application source code. running test suites and building archive files. moving/copying files to server machines. interacting with source control systems.